Type of oral cortiosteroid in mild to moderate croup. Issue 3 (1st May 2003) - Corfield, A; Teece, S
Abstract : A short cut review was carried out to establish whether oral dexamethasone is better than oral prednisolone at improving outcome in children with mild to moderate croup. Altogether 139 papers were found using the reported search, of which none presented any evidence to answer the clinical question. It is concluded that there is no evidence available to answer this question. Further research is needed.